2014
DOI: 10.1158/1055-9965.epi-14-0114
|View full text |Cite
|
Sign up to set email alerts
|

No Association of Plasma Levels of Adiponectin and c-peptide with Risk of Aggressive Prostate Cancer in the Cancer Prevention Study II Nutrition Cohort

Abstract: Background: Obesity is associated with a higher risk of aggressive prostate cancer and alters circulating levels of insulin and adiponectin, two hormones that influence biologic processes implicated in carcinogenesis. Results of some studies showed associations of circulating levels of adiponectin, insulin, and c-peptide (a marker of insulin secretion) with aggressive prostate cancer, but the size of these studies was limited.Methods: A nested case-control study of 272 aggressive prostate cancer cases [Gleason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Furthermore, reduced APN levels were associated with tumor stage in obese and overweight men, but not in normal weight men or overall in all men 135 . Other studies have also found no significant association between APN levels and PrC risk 136,137 .…”
Section: Prostate Cancer (Prc)mentioning
confidence: 84%
“…Furthermore, reduced APN levels were associated with tumor stage in obese and overweight men, but not in normal weight men or overall in all men 135 . Other studies have also found no significant association between APN levels and PrC risk 136,137 .…”
Section: Prostate Cancer (Prc)mentioning
confidence: 84%
“…In a pro-spective cohort with prediagnostic bloods, men who had high-circulating levels of C-peptide, a marker of insulin secretion, had an increased cancer-specific mortality (Ma et al 2008). However, this association was not confirmed in two prospective studies for risk of aggressive disease (Ma et al 2008;Stevens et al 2014).…”
Section: Risk Factors For Advanced and Fatal Prostate Cancermentioning
confidence: 99%
“…A recent meta-analysis did not find an increased risk of breast cancer in women with elevated serum insulin or C-peptide levels after adjusting for BMI, suggesting that insulin and C-peptide levels are not independent of BMI (9). In prostate cancer, some studies, including the Health Professionals Follow-Up Study and the CPS II Nutrition cohort, have reported no clear correlation between circulating C-peptide and either prostate cancer risk, or mortality, or in the risk of developing aggressive prostate cancer (107,124,177). However, the Physicians Health Study reported that obese men with elevated C-peptide levels were four times more likely to die from prostate cancer than men with normal C-peptide levels (124).…”
Section: Epidemiology Linking Hyperinsulinemia and Cancermentioning
confidence: 99%